Fostering Resilience and Wellness: The Synergy of Mindful Eating and the Mediterranean Lifestyle - Efstratios Christodoulou; Georgia-Eirini Deligiannidou; Christos Kontogiorgis; Constantinos Giaginis; Antonios E. Koutelidakis (Applied Biosciences, 2024)
Increasing evidence indicates that the cultivation of mindful eating, adherence to the Mediterranean lifestyle, and the development of psychological resilience may contribute to the enhancement of overall health and well-being. The purpose of this study was to explore the association between mindful eating and the Mediterranean lifestyle in relation to psychological resilience and the maintenance of a healthy weight. In the framework of a cross-sectional study, 288 individuals voluntarily took part in an online research survey conducted in Greece. Results showed that both mindful eating and the Mediterranean diet were significantly correlated (p < 0.001) with psychological resilience. Multiple regression models identified mindful eating and the Mediterranean diet as predictive factors of psychological resilience (p < 0.001). There was a statistically significant (p < 0.05) intercorrelation between mindful eating, the Mediterranean diet, and psychological resilience. Following the application of multiple regression models, mindful eating and Mediterranean diet were identified as predictive factors of psychological resilience (p < 0.0001). Individuals with a normal Body Mass Index (BMI) displayed stronger adherence to mindful eating and the Mediterranean lifestyle, in contrast to those classified in the overweight and obesity BMI groups. People with higher mindful eating scores had 14% better odds of maintaining their weight loss after a weight-reducing diet than those with a lower mindful eating score (OR: 1.142, 95% CI: 1.084, 1.204, p < 0.0001). In summary, the integration of mindful eating and the Mediterranean lifestyle may represent a feasible approach to bolstering psychological resilience, overall health, and well-being.